Transfer Pricing and Debt Shifting in Multinationals - Dirk Schindler; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2013)
There is a growing concern that governments lose substantial corporate tax revenue because of profit shifting through transfer-pricing and thin-capitalization strategies. Existing literature studies profit shifting and transfer pricing separately. In practice, the choice of debt-to-asset ratios in affiliates and the transfer price of debt are interrelated management decisions that are also mutually affected by government regulation. This paper models these strategies as intertwined. We find that the tax sensitivity of the corporate tax base depends on whether the debt shifting and transfer pricing are cost complements or substitutes. A second result is that stricter regulation of debt shifting (transfer pricing) can potentially increase the use of transfer pricing (debt shifting) and thus the amount of profits shifted.
Keywords: H25; F23; D21; 330; multinational corporations; profit shifting; debt shifting; concealment costs